2018
DOI: 10.1186/s13256-018-1667-2
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab combined with stereotactic body radiotherapy in a patient with human immunodeficiency virus and advanced non-small cell lung cancer: a case report

Abstract: BackgroundPembrolizumab has significantly improved outcomes in patients with advanced non-small cell lung cancer. Combining programmed death-1 inhibitor with stereotactic body radiotherapy showed a slight toxicity and good benefits in recent clinical trials. However, patients infected with human immunodeficiency virus were excluded from most trials because it was assumed that their anti-tumor immunity was compromised compared with immunocompetent patients.Case presentationIn June 2016, a 52-year-old Chinese ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…31 Some of the used agents are Ipilimumab. [32][33][34][35] Nanomedicine is the use of nanotechnology in medical science. It refers to the manipulation of size and shape of a material at the nano-level (1-100 nm).…”
Section: The Era Of Personalized Medicinementioning
confidence: 99%
“…31 Some of the used agents are Ipilimumab. [32][33][34][35] Nanomedicine is the use of nanotechnology in medical science. It refers to the manipulation of size and shape of a material at the nano-level (1-100 nm).…”
Section: The Era Of Personalized Medicinementioning
confidence: 99%
“…Li et al . reported that a patient with HIV infection and non‐small cell lung cancer was treated with pembrolizumab and SBRT, and then experienced massive pericardial effusion and interstitial pneumonia . However, this case failed to explain the relationship between HIV infection and AEs.…”
Section: Safety Of Icis In Patients With Immune System Impairmentmentioning
confidence: 90%
“…Most patients required discontinuation of therapy completely for a short period of time as well as immunosuppressant treatment. (32) Vitiligo (1), granuloma annulare (2), bullous pemphigoid (3), psoriasis (22), erythema multiforme (1), lichenoid reaction (2), Grover's disease (1) Endocrinologic (52) Type 1 diabetes mellitus (38), hypophysitis (9), isolated adrenal insufficiency (1), thyroid storm (2), hypothyroidism (2) Gastrointestinal (47) Acute liver failure (1), hepatitis (8), bile duct obstruction (1), cholangitis (1), pancreatitis (1), hemorrhagic gastritis (1), ileitis (1), colitis (32), intestinal obstruction (1) Pulmonary (11) Organizing pneumonia (5), sarcoidosis (2), pneumonitis (4) Neurologic (20) Myasthenia gravis (5), Guillain-Barre syndrome (3), cerebral edema (1), necrotizing encephalopathy (1), encephalitis (2), mononeuropathy multiplex with rhabdomyolysis (1), necrotic myelopathy (1), Bell's palsy (1), inflammation enteric neuropathy (1), brachial plexus neuritis (2), peripheral neuropathy (2) Cardiac (7) Myocarditis (2), cardiomyopathy (1), coronary spasm (1), pericardial effusion (3) Rheumatologic (28) Remitting seronegative symmetrical synovitis with pitting edema (1), arthritis (12), dermatomyositis/myositis (4), Goodpasture's disease (1), scleroderma (2), polymyalgia rheumatic (3), sicca syndrome (5) Nephrotic (7) Cystitis (1), renal failure (1), nephrotic syndrome (4), acute glomerulonephritis (1) Hematologic (16) Pancytopenia (2), neutropenia (6), aplastic anemia (2), pure red cell aplasia (1), thrombocytopenia (3), acute thrombosis (1), hemophagocytic lymphohistiocytosis (1) Ophthalmologic (17) Uveitis (7), Vogt-Koyanagi-Harada disease-like uveitis (2), orbital inflammation (3), dry eye (2), ulcerative keratitis (1), ocular myositis (2) Otorhinolaryngologic (2) Sinusitis…”
Section: Toxicity Profilementioning
confidence: 99%
“…It is not clear whether the stereotactic body radiotherapy and pembrolizumab interaction was the cause of these events. 65 Surgery is a primary part of treatment for solid tumor malignancies such as lung, anal, prostate, liver, and breast cancers. In the modern ART era, some experts believe that the overall health or performance status is a more reliable indicator of successful surgical outcomes than CD4 count or viral load in PLWH, and that HIV status should not affect choices about surgery.…”
Section: Management Of Malignancy In Plwhmentioning
confidence: 99%
“…64 However, data are more limited in other cancers and in combination with immunotherapies. 10,65 A 52-year-old man with NSCLC experienced pericardial effusion and interstitial pneumonia after 5 weeks of stereotactic body radiotherapy and 3 cycles of pembrolizumab. After the interruption of pembrolizumab, tumor growth progressed.…”
Section: Management Of Malignancy In Plwhmentioning
confidence: 99%